RFE, BOXCOX, AND PCA COMPARISON FOR MULTICLASS CLASSIFI-CATION SUPPORT VECTOR MACHINE OPTIMIZATION - Indrawata Wardhana; Vandri Ahmad Isnaini; Rahmi Putri Wirman (STMIK Royal, 2022)
Abstract: The technique of multiclass classification based on SVMs has been widely used. SVM optimization will be accomplished by examining the extraction features of Principal Component Analysis (PCA), Box-Cox Transformation, and Recursive Feature Elimination (RFE). The dataset contains 13,611 rows and 17 variables, generated from the UCI repository's multiclass dry bean data. Barbunya, Bombay, Cal, Dermas, Horoz, Seker, and Sira are just a few of the dry bean kinds available. The dataset was tested using SVM Linear kernel and SVM Radial Basis.According to the results, the combination of scale-center-BoxCox-SVM Radial extraction achieves the maximum accuracy of 93.16 percent and the shortest processing time of 6.10 minutes. 96.00 percent, 100 percent, 96.71 percent, 95.16 percent, 97.60 percent, 97.74 percent, and 91.95 percent, according to bean class.RFE-SVM Radial has a 91.18 percent accuracy and a processing time of 6.55 minutes. BoxCox outperforms conventional techniques in terms of prediction accuracy while requiring less training time. Keywords: Bean, PCA, BoxCox, SVM, RFE Abstrak: Klasifikasi Multikelas menggunakan SVM telah banyak digunakan. Pada penelitian ini akan diuji fitur ekstraksi Principal Component Analysis, Box Cox Transformation dan fitur eliminisi Recursive Feature Elimination untuk mendapatkan optimasi SVM. Dataset berasal dari data multikelas kacang kering UCI repository dengan jumlah 13.611 baris dan 17 variabel. Kelas kacang kering yakni : Barbunya, Bombay, Cal, Dermas, Horoz, Seker dan Sira. Dataset diuji menggunakan kernel SVM Linier dan SVM Radial Basis. Didapatkan hasil, bahwa kombinasi fitur ekstraksi : scale-center-BoxCox-SVM Radial memiliki akurasi terbaik yakni 93,16% dan waktu proses 6,10 menit. Klasifikasi berdasarkan kelas kacang berturut-turut 96,00%,100%, 96,71%, 95,16%, 97,60%, 97,74% dan 91,95%. RFE- SVM Radial hanya memberikan akurasi sebesar 91,18 % dengan waktu proses sebesar 6.55 menit. Penggunaan BoxCox dibandingkan dengan lainnya, memberikan hasil prediksi lebih baik dan namun tidak mempercepat waktu pelatihan. Kata kunci: BoxCox; Kacang; PCA; RFE; SVM